Օսմանյան բանակի և այլ զինված կազմավորումների կողմից հայերի ինքնապաշտպանության ճնշումն ու հայկական բնակավայրերի ոչնչացումը - Աշխեն Բասենցյան (ՀՀ ԳԱԱ հրատ.)
Османская армия и другие вооруженные формирования принимали непосредственное участие в подавлении самообороны и уничтожении армян. Османское правительство выделяло армейские подразделения только тогда, когда сил жандармерии и других вооруженных формирований было недостаточно для подавления самообороны и уничтожения поселения. The Ottoman army and other armed formations as well directly participated in the suppression of the Armenians’ self-defense and their destruction. The Ottoman government separated the army into units only when the forces of the gendarmerie and other armed formations were insufficient to suppress the Armenian self-defense and the destruction of their settlements.
Keywords: Armenian Massacres